The Urgency of Digital Literacy Learning in Educational Units: Systematic Literature Review - Ketut Agustini; Gede Rasben Dantes; I Gde Wawan Sudatha; Hadi Pradana, Pascalian (Universitas Nahdlatul Ulama Surabaya, 2024)
In this millennial era, it is very important to use digital literacy in education. The problem of education in the current digital era is that students do not have equal access to reading materials and their interest in reading is low. Thus, the aim of this research is to study the importance, causes, efforts and challenges associated with implementing digital literacy learning in educational units. The methods used are Systematic Literature Review (SLR) and bibliometric analysis. The data source uses article search criteria from 2021 to 2024 with the Publish or Perish application, based on SCOPUS sources with the title words being digital literacy learning. Data collection used the PRISMA procedure, 200 articles were obtained from the database and then the screening process was carried out so that 14 articles were included. Research results show that digital literacy in education does not only include teaching technology skills but also prepares future generations to think critically, communicate well, collaborate and be creative in the era of digital globalization. Implementing digital literacy in educational units can develop more efficient learning models and media to face current technological challenges by using applications that are also integrated with local wisdom and prepare students for a future that is increasingly connected to technology. Further research focuses on creating more efficient learning models to prepare future generations to face the challenges of the technological era.